Intraperitoneal infusion of mesenchymal stem cell attenuates severity of collagen antibody induced arthritis. - Yoojun Nam; Seung Min Jung; Yeri Alice Rim; Hyerin Jung; Kijun Lee; Narae Park; Juryun Kim; Yeonsue Jang; Yong-Beom Park; Sung-Hwan Park; Ji Hyeon Ju (PLoS ONE)
It is unclear how systemic administration of mesenchymal stem cells (MSCs) controls local inflammation. The aim of this study was to evaluate the therapeutic effects of human MSCs on inflammatory arthritis and to identify the underlying mechanisms. Mice with collagen antibody-induced arthritis (CAIA) received two intraperitoneal injections of human bone marrow-derived MSCs. The clinical and histological features of injected CAIA were then compared with those of non-injected mice. The effect of MSCs on induction of regulatory T cells was examined both in vitro and in vivo. We also examined multiple cytokines secreted by peritoneal mononuclear cells, along with migration of MSCs in the presence of stromal cell-derived factor-1 alpha (SDF-1α) and/or regulated on activation, normal T cell expressed and secreted (RANTES). Sections of CAIA mouse joints and spleen were stained for human anti-nuclear antibodies (ANAs) to confirm migration of injected human MSCs. The results showed that MSCs alleviated the clinical and histological signs of synovitis in CAIA mice. Peritoneal lavage cells from mice treated with MSCs expressed higher levels of SDF-1α and RANTES than those from mice not treated with MSCs. MSC migration was more prevalent in the presence of SDF-1α and/or RANTES. MSCs induced CD4+ T cells to differentiate into regulatory T cells in vitro, and expression of FOXP3 mRNA was upregulated in the forepaws of MSC-treated CAIA mice. Synovial and splenic tissues from CAIA mice receiving human MSCs were positive for human ANA, suggesting recruitment of MSCs. Taken together, these results suggest that MSCs migrate into inflamed tissues and directly induce the differentiation of CD4+ T cells into regulatory T cells, which then suppress inflammation. Thus, systemic administration of MSCs may be a therapeutic option for rheumatoid arthritis.